Central auditory processing outcome after stroke in children - Karla M. I. Freiria Elias; Carolina Camargo Oliveira; Marina Junqueira Airoldi; Katia Maria D. Franco; Sônia das Dores Rodrigues; Sylvia Maria Ciasca; Maria Valeriana L. Moura-Ribeiro (Arquivos de Neuro-Psiquiatria)
Objective To investigate central auditory processing in children with unilateral stroke and to verify whether the hemisphere affected by the lesion influenced auditory competence. Method 23 children (13 male) between 7 and 16 years old were evaluated through speech-in-noise tests (auditory closure); dichotic digit test and staggered spondaic word test (selective attention); pitch pattern and duration pattern sequence tests (temporal processing) and their results were compared with control children. Auditory competence was established according to the performance in auditory analysis ability. Results Was verified similar performance between groups in auditory closure ability and pronounced deficits in selective attention and temporal processing abilities. Most children with stroke showed an impaired auditory ability in a moderate degree. Conclusion Children with stroke showed deficits in auditory processing and the degree of impairment was not related to the hemisphere affected by the lesion.